The Social Role of Cooperatives in Residents' Economic Empowerment: A Qualitative Study in the Cirebon Traditional Fishermen Community - Irfan Azis; Upit Elya Rohimi (Sekolah Tinggi Agama Islam Kuningan, 2025)
Traditional fishing communities are among the most economically vulnerable groups, especially amidst the pressures of climate change, limited market access, and the dominance of middlemen. In the midst of these challenges, cooperatives are present as an alternative economic institution that has the potential to strengthen the bargaining power and solidarity of coastal communities. This study aims to examine the social role of cooperatives in the process of economic empowerment of traditional fishing communities in Cirebon. The method used is qualitative with a case study approach, through in-depth interviews, participatory observation, and documentation of active cooperative members. The results show that cooperatives not only function as providers of access to capital, but also as reinforcers of social solidarity, spaces for democratic participation, and means of local economic transformation that reduce dependence on middlemen. Cooperatives encourage collective behavioral change and shape a more equitable socio-economic structure. The implications of this research support the development of community-based policies and the expansion of social-based cooperative models to improve the economic resilience of coastal areas. In addition, this study opens up opportunities for further research on cooperative digitalization and adaptive cooperative models in the era of a sustainable maritime economy.